Improvement of Coplanar Vivaldi Antenna Radiation Patterns with Fractal Structure for Ultra-Wideband Applications - Rizqi Agustini; Nurhayati Nurhayati (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2021)
The need for telecommunications technology requires fast data transfer and increasing capacity. Therefore, telecommunications technology continues to be developed by creating transmitter and receiver devices that can work at Ultra-Wideband (UWB) frequencies. This study aims to design a coplanar Vivaldi antenna with a fractal structure so that the performance of the antenna radiation pattern can increase to apply UWB frequency. The conventional coplanar Vivaldi antenna, model-A, and Model-B fractal antennas are designed to see the performance of return loss values less than -10 dB, VSWR less than 2, and working frequency of 2-10 GHz. The fractal model is created with a circular repeating structure given at the edges of the antenna patch. From the simulation results, the main lobe value of the conventional Coplanar Vivaldi antenna was 5.21 dBi, the model-A fractal was 7.02 dBi, and the Model-B fractal was 7.84 dBi. The order of the best sidelobe performance at a frequency of 6 GHz is obtained for the model-A fractal of -9 dB. Beamwidth of 46 degrees and the best main lobe direction of 0 degrees is obtained for fractal model-B. By adding a fractal structure, the lobe magnitude/directivity, sidelobe level, beamwidth, and main lobe direction can be improved